Bridging transcultural divides Asian languages and cultures in global highter education - Song, Xianlin; Cadman, Kate (The University of Adelaide Press, 2012)
The impressive and stimulating essays in Bridging Transcultural Divides deal with the cultural and educational issues in the Australian context. The books central message is that education for Asian students in Australia, and more broadly in the West, can no longer been seen as a one-way transfer of knowledge, but must be understood as a process of reciprocal learning in which both teachers and students are changed by the experience
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Oriental languages / Study and teaching (Highter); Asien; Asia / Civilization / Study and teaching (Highter); Asia / Civilization / Study and teaching (Higher)